Human-Like Motion Generation and Control for Humanoid's Dual Arm Object Manipulation - Shin, Sung Yul; Kim, ChangHwan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
The robot manipulation in human environment is a challenging issue because the human environment is complex, dynamic, unstructured, and difficult to perceive reliably. In order to implement promising robot applications in our daily lives, robots need to perform manipulation tasks within human environment. Particularly for a humanoid robot, the manipulability of the objects is essential to assist the humans in human environment. This paper presents a method for manipulating an object with both arms of a humanoid robot. We focus on the generation of human-like movements by using the human motion capture data. Then, the control method based on the virtual dynamics model is proposed to control both the motion and force under the uniform control system. This method empowers the robot to perform the object manipulation task including reaching, grasping, and moving an object in sequence. The proposed algorithm is implemented on a humanoid robot with independent joint controller at each motor; its performance is demonstrated by manipulating an object with both arms.
Keywords: ROBOTS; MOVEMENTS; GRASP; TASK; PAIR